2013 IEEE Antennas and Propagation Society International Symposium (APSURSI) 2013
DOI: 10.1109/aps.2013.6711335
|View full text |Cite
|
Sign up to set email alerts
|

Design of a reflectarray antenna at 300 GHz based on cells with three coplanar dipoles

Abstract: Abstract-Simulated results are presented for a reflectarray antenna designed to produce a collimated beam at 300 GHz within a 13% bandwidth. The reflectarray cells are made of three parallel dipoles printed on one side of a 110-um Quartz wafer coated with a conductive ground plane on the back side, where the phase is adjusted by varying the length of the dipoles. A practically linear phase variation is achieved in a range greater than 360° and frequencies from 280 GHz to 320 GHz. A reflectarray antenna was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…The active dipole element resonates at 300 GHz with maximum gain of 9.12 dBi and also provides a bandwidth of 46 GHz from 294 GHz to 340 GHz as shown in Figure 3. 180 µm D 5 170 µm D 6 162 µm The optimization of gain and bandwidth with different numbers of directors. Further enhancement in the gain and directivity can be obtained with the modification of substrate in the form of a lens, and this technique is discussed in Section 3.…”
Section: Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active dipole element resonates at 300 GHz with maximum gain of 9.12 dBi and also provides a bandwidth of 46 GHz from 294 GHz to 340 GHz as shown in Figure 3. 180 µm D 5 170 µm D 6 162 µm The optimization of gain and bandwidth with different numbers of directors. Further enhancement in the gain and directivity can be obtained with the modification of substrate in the form of a lens, and this technique is discussed in Section 3.…”
Section: Elementsmentioning
confidence: 99%
“…The design and criteria to enhance the gain and bandwidth of the antennas at higher frequencies are detailed in [4]. For the bandwidth extension and reduction in the reflection losses, the novel technologies in the field of reflect array antennas at 300 GHz were developed in [5,6]. Since it is hard to limit the reflections around the high frequency resonances, there will be poor reflection loss characteristics at 300 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Posteriormente, três dipolos paralelos com comprimentos diferentes são avaliados. Essa geometria foi proposta por [6], [7] e [8] visando aumentar a faixa de variação de fase. Aqui, células são projetadas na frequência de 8,6 GHz, que corresponde a faixa de frequência alocada para a exploração da terra a partir de satélites.…”
Section: Introductionunclassified
“…It was found that a reflection phase range of greater than 360° was easily obtainable by cascading multiple hexagonal rings [4] concentrically. Dipole was used for reflectarray design in [13], [14], and it was found that placing a couple of dipolar strips in parallel had made possible linear phase response with a phase range of more than 360°.…”
Section: Introductionmentioning
confidence: 99%